A structural explanation for enhanced binding behaviors between β-lactoglobulin and alkene-aldehydes upon heat- and ultrasonication-induced protein unfolding. (September 2022) - Xu, Le; Zheng, Yuanrong; Zhou, Changyu; Pan, Daodong; Geng, Fang; Cao, Jinxuan; Xia, Qiang
Abstract: This investigation aims to elucidate the binding behaviors between alkene-aldehydes (AAs) and β -lactoglobulin (BLG), and a structural explanation responding to ultrasonic (US) and heat (HT) treatments was proposed. Upon US- and HT-treatments, the conformational evolution of BLG was evidenced by multi-spectroscopic techniques during which the formation of molten globule-state-like protein (MGSP) enhanced the binding affinity of AAs to protein, positively correlated with the unfolding extent of MGSP. Moreover, both of treatments were capable of inducing production of novel sites on outer surface and central cavity of BLG for AAs binding, accompanied with the formation process of MGSP. Comparatively, US-treatment dynamically modulated the conformation of gate of central cavity which was easier to promote AAs binding into the internal sites of BLG. According to NMR and LC-MS/MS results, the processes-induced MGSP formation possibly contributed to the covalent binding between AAs and BLG through the pathways involving Michael addition and Schiff-based reactions. These results demonstrated a close association of HT- and US-treatments induced MGSP with the release and retention behaviors of volatile aromas, potentially acting as a structure carrier designed to re-formulate and develop flavor features. Graphical abstract: Image 1 Highlights: Ultrasound and heat induced molten globule-state-like protein (MGSP) formation. Processes-induced MGSP presented higher binding affinity of alkene-aldehydes (AAs). Binding sites of AAs-MGSP were identified using LC-MS/MS and 2D NMR. Hydrophobic interaction, Michael addition and Schiff-based reaction dominated in AAs-MGSP binding. Ultrasound promoted AAs easier binding into interior cavity sites than heating.